Criminological Perspective in Crime Prevention of Land Grabbing - Junimart Girsang; Gunarto Gunarto; Al Amin (Jurnal Hukum, 2024)
Land grabbing, a pervasive issue with significant social, economic, and environmental consequences, is often rooted in unlawful land appropriation, highlighting the need for effective legal reforms and policy implementation. This study explores the issue of land grabbing in Indonesia from a criminological perspective, focusing on the intersection of criminal law enforcement and social policy. The research aims to analyze the causes, effects, and potential solutions to land grabbing, with a particular emphasis on social defense and justice. Using a normative juridical approach, the study examines relevant legal norms, regulations, and frameworks, which address land grabbing and its law enforcement. Findings suggest that a comprehensive approach involving legal enforcement, public education, improved land administration, and active community participation is essential to reduce land grabbing. The study concludes that a balanced integration of legal measures and social interventions is necessary to protect property rights, promote justice, and create a fairer and more stable environment for land ownership in Indonesia.